Naringenin as potent anticancer phytocompound in breast carcinoma: from mechanistic approach to nanoformulations based therapeutics - Elsori, Deena; Pandey, Pratibha; Ramniwas, Seema; Kumar, Rahul; Lakhanpal, Sorabh; Rab, Safia Obaidur; Siddiqui, Samra; Singh, Ajay; Saeed, Mohd; Khan, Fahad (Frontiers in Pharmacology, 2024)
The bioactive compounds present in citrus fruits are gaining broader acceptance in oncology.Numerous studies have deciphered naringenin's antioxidant and anticancer potential in human and animal studies. Naringenin (NGE) potentially suppresses cancer progression, thereby improving the health of cancer patients. The pleiotropic anticancer properties of naringenin include inhibition of the synthesis of growth factors and cytokines, inhibition of the cell cycle, and modification of several cellular signaling pathways. As an herbal remedy, naringenin has significant pharmacological properties, such as anti-inflammatory, antioxidant, neuroprotective, hepatoprotective, and anti-cancer activities. The inactivation of carcinogens following treatment with pure naringenin, naringenin-loaded nanoparticles, and naringenin combined with anti-cancer agents was demonstrated by data in vitro and in vivo studies. These studies included colon cancer, lung neoplasms, breast cancer, leukemia and lymphoma, pancreatic cancer, prostate tumors, oral squamous cell carcinoma, liver cancer, brain tumors, skin cancer, cervical and ovarian cancers, bladder neoplasms, gastric cancer, and osteosarcoma. The effects of naringenin on processes related to inflammation, apoptosis, proliferation, angiogenesis, metastasis, and invasion in breast cancer are covered in this narrative review, along with its potential to develop novel and secure anticancer medications.